HUBUNGAN PELAYANAN TENAGA KESEHATAN DENGAN TINGKAT KEPUASAN MASYARAKAT DALAM KEGIATAN VAKSINASI DI PUSKESMAS PAYUNG SEKAKI - Anggreny, Yecy; Mayang Sari, Siska; Niriyah, Sekani (Coping: Community of Publishing in Nursing; Vol 10 No 6 (2022): Desember 2022DO - 10.24843/coping.2022.v10.i06.p05, 2022)
Vaccination activities in service activities were one of the government's breakthroughs in suppressing the transmission of COVID-19. One of the problems that arise during vaccination activities was community satisfaction. The purpose of this study was to determine the relationship between health worker services and the level of community satisfaction in vaccination activities at the Payung Sekaki Public Health Center. The research method used is a type of analytical quantitative research, with a correlation design and a cross-sectional approach. The research was conducted at the Payung Sekaki Public Health Center. The population in the study was people who received the vaccine in the Payung Sekaki Public Health Center totaling 10.279 people. The sampling technique used is purposive sampling with the number of samples needed was 271 people. Data collection in this study used a health service questionnaire and a satisfaction questionnaire that had been tested for validity before. Data was analyzed by using univariate and bivariate analysis. The results of the bivariate analysis using continuity correction found that the relationship between health workers' services and the level of community satisfaction in vaccination activities (p-value = 0,000) with the dimension of justice was the most influential factor in community satisfaction. Quality health services provided by health workers can increase public satisfaction with COVID-19 vaccination activities.